(3GdHjGfs - (3GdYGedj GdfHWj GdLRjfi, TeS GdOjf, GdTgjO GdChd, eMeO Hf eci Hf eMeO Hf MGeO, J (B786 (3g`s ((3CUagGfs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeOG jSJOQ CNdGb cQeg hjSJeWQ TBHjH fYeg(B...(3CeG HYO aEf GdCOdI GdYbdjI hGdfbdjI eJWGHbI Ydi TQa GdYdhe(B...(3hgPG GdHjGf cGad HGdege hGdeMJhe Ydi WQjbI GdYJQI GdWGgQI(B...(3cJGH GdWgGQI(B...s
(3BNQgG (B:s
(3jfJgj HChd cJGH GdUjGe hBNQg(B: ...(3hef gPG CHjf Cf GdUhe efbhd Yf eYfGg GddZhj hdG jdRe GdYGej eYQaI Pdc(B...(3hajg eWdHGf GdChd(B: (3ajeG jeSc Yfg hgh CbSGe(B: (3GdGHJdGY jLH ajg Edi gGgfG GfJgi cdGe GdeUfa(B...s
(3jfJgj HChd cJGH GdUjGe dCf eDdag eGJ bHd Cf jJeg(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B109s
(3eYLe Gdehdajf(B:(3L(B3(3,U(B731s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis